2017
DOI: 10.1093/ve/vex003
|View full text |Cite
|
Sign up to set email alerts
|

In vivo mutation rates and the landscape of fitness costs of HIV-1

Abstract: Mutation rates and fitness costs of deleterious mutations are difficult to measure in vivo but essential for a quantitative understanding of evolution. Using whole genome deep sequencing data from longitudinal samples during untreated HIV-1 infection, we estimated mutation rates and fitness costs in HIV-1 from the dynamics of genetic variation. At approximately neutral sites, mutations accumulate with a rate of 1.2 × 10−5 per site per day, in agreement with the rate measured in cell cultures. We estimated the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
119
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(136 citation statements)
references
References 71 publications
10
119
5
Order By: Relevance
“…Most diversity in pol is synonymous and accumulates at 3rd codon positions, while diversity at 1st and 2nd codon positions remained low throughout. This pattern was less pronounced in other genes [24, 37] (see also S1 and S2 Figs). In env , in particular, frequent selective sweeps result in a saturation of diversity later in infection [17, 24].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Most diversity in pol is synonymous and accumulates at 3rd codon positions, while diversity at 1st and 2nd codon positions remained low throughout. This pattern was less pronounced in other genes [24, 37] (see also S1 and S2 Figs). In env , in particular, frequent selective sweeps result in a saturation of diversity later in infection [17, 24].…”
Section: Resultsmentioning
confidence: 90%
“…The 1st and 2nd codon positions tend to be conserved since they result in mostly non-synonymous mutations. Depending on the fitness cost associated with the mutation, diversity at these sites saturates at different levels [37]. As the threshold x c is lowered, sites with higher and higher fitness costs contribute to the diversity measures and the effect of the saturation behavior becomes more pronounced.…”
Section: Resultsmentioning
confidence: 99%
“…Most diversity in pol is synonymous and accumulates at 3rd codon 129 positions, while diversity at 1st and 2nd codon positions remained low throughout. This 130 dichotomy was less pronounced in other genes [22,30] (see also S1 Fig and S2 Fig). In 131 env in particular frequent selective sweeps limit diversity later in infection [16,22].…”
mentioning
confidence: 92%
“…We show that sequence diversity is a 28 useful biomarker that grows approximately linearly with time during the first 8 years of 29 infection. We found that the pol gene was best suited to calculate TI because diversity, 30 mostly at third positions, accumulated more steadily in pol than in other genomic 31 regions. Inclusion of intra-patient single nucleotide variants (iSNVs, also referred to as 32 "polymorphisms") down to the detection limit of NGS (i.e.…”
mentioning
confidence: 95%
See 1 more Smart Citation